CHARACTERISTICS OF SPATIAL CAPABILITY OF GEOGRAPHIC STUDENTS OF PGRI PALEMBANG UNIVERSITY - SITI ASIYAH (GeoEco, 2019)
Spatial ability is an important spatial intelligence possessed by geography education students. with this ability, students' thinking can develop while learning geography. The characters of spatial ability of students differ from one another. In this research the researcher will discuss the character of the spatial ability of geography education students, amounting to 27 students. The method used in this research is descriptive qualitative method. Characteristics of students' spatial ability are seen from the results of tests on basic cartography courses. The test was made with 12 essay questions with criterion questions from the cognitive domain according to Taxonomy Bloom. Of the six cognitive criteria, three criteria were taken, namely remember, understand, and apply. The results on the criteria remember all students can answer correctly, then on the criteria to understand the average value has decreased by 17, and the criteria to apply the average value to 13.